A split‐step‐scheme‐based precise integration time domain method for solving wave equation. (2014) - ,; ,; ,; ,
Abstract : Purpose – This paper aims to present a modified precise integration time domain (PITD) method for the numerical solution of 2D scalar wave equation.Design/methodology/approach – The split step (SS) scheme is applied to factorize the conventional PITD calculation into two sub‐steps procedures and then field components can be updated along one spatial direction only in each sub‐step. The perfectly matched layer (PML) absorber is extended to this method for modeling open region problems by using the stretched coordinate approach.Findings – It is shown that this method requires less computation time and storage space in comparison with the conventional PITD method, yet maintains the numerical stability despite using large time steps.Research limitations/implications – The WE‐PITD method requires the divergence free region, which may be a limit on its usage. Hence, there is a challenge of using this technique in the 3D problems.Originality/value – Based on the SS scheme, the PITD method is used to solve the scale wave equation rather than Maxwell's equations, leading to a significant reduction in the computation time and memory usage. Acknowledgements : This work was supported by the National Natural Science Foundation of China under Grant No. 50877055.